2002
DOI: 10.1108/eb021210
|View full text |Cite
|
Sign up to set email alerts
|

Risk management trends in the construction industry: moving towards joint risk management

Abstract: This paper reports the outcomes of the first of three planned questionnaire surveys in the first phase of a broader Hong Kong based study on ‘Joint Risk Management’ (JRM). The survey compared perceptions on both present and preferred risk allocation, including JRM, in construction contracts. Data was mainly collected in Hong Kong and mainland China (with most respondents having working experience from Hong Kong) from various professionals and practitioners representing broad groups of academics, consultants, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…This stance can be explained from the fact that typically contractors are allocated an excessive number of risks which make them feel unfairly treated (Perez et al, 2017;Zhang et al, 2016). Similar findings have been reported by Rahman and Kumaraswamy (2002a) who observe that owners were seen to be more ready than contractors to approach JRM. This feeling is further justified taking into account Li et al's (2005) observation that there are risks not clearly related to the project characteristics, for which it is likely that no party has the required experience to manage them.…”
Section: Results and Analysissupporting
confidence: 62%
See 3 more Smart Citations
“…This stance can be explained from the fact that typically contractors are allocated an excessive number of risks which make them feel unfairly treated (Perez et al, 2017;Zhang et al, 2016). Similar findings have been reported by Rahman and Kumaraswamy (2002a) who observe that owners were seen to be more ready than contractors to approach JRM. This feeling is further justified taking into account Li et al's (2005) observation that there are risks not clearly related to the project characteristics, for which it is likely that no party has the required experience to manage them.…”
Section: Results and Analysissupporting
confidence: 62%
“…In this respect, Osipova and Eriksson (2013) highlight the fact that traditional RM entails separate risk identification and assessment from each project party which may lead to a narrow and biased perspective of risk. Rahman and Kumaraswamy's (2002a) survey findings also confirm that standard conditions of contracts often fall short in conveying an unambiguous and unique message to all contracting parties for efficient risk management.…”
Section: Jedt 182mentioning
confidence: 55%
See 2 more Smart Citations
“…It implies contracting risk allocation such that all stakeholders can take part and help with managing risks even after the formal assignment of responsibilities. Research conducted in Hong Kong [14] indicated that investors and managers were more likely to accept this strategy when compared with contractors and engineers. Results of research that was conducted in the UK five years prior to the study in Pakistan indicated that managers mostly relied on their own knowledge and experience to achieve the best results.…”
Section: Ebsco Database-review Of Risk Management Practicesmentioning
confidence: 99%